2017
DOI: 10.7717/peerj.3330
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effect of fluoxetine on the response to physical or chemical stressors in zebrafish

Abstract: Fluoxetine is a selective serotonin reuptake inhibitor that increases serotonin concentration in the central nervous system and modulates various systems, including the control of sympathetic outflow and the hypothalamus-pituitaryadrenal. However, it is not yet established whether fluoxetine can modulate the responses to stressors stimulants (physical or chemical) that trigger cortisol response in zebrafish. We demonstrate that fluoxetine blunts the response to physical stress, but not to chemical stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
(54 reference statements)
1
25
0
Order By: Relevance
“…Both the ATN Several hypothalamic regions of teleosts, including ATN and VTN, are connected to the Vs (Folgueira et al, 2004), which has been proposed as homologous to the medial amygdala (Biechl et al, 2017) (Kysil et al, 2017), and subordinate-dominant interactions (Pavlidis et al, 2011). CAS also elicits increases in cortisol responses in Nile tilapia (Silva et al, 2015) and zebrafish (Abreu et al, 2017a;Schirmer et al, 2013); interestingly, cortisol responses are also observed after visual contact with a predator in zebrafish (Barcellos et al, 2010(Barcellos et al, , 2007, and D. rerio also appears to be able to communicate predation risk to conspecifics, since cortisol responses are observed after seeing a shoalmate displaying antipredator behavior (Oliveira et al, , 2013. zebrafish lineage (gr s357 ) with non-functional glucocorticoid receptors.…”
Section: Hypothalamic Circuits For Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Both the ATN Several hypothalamic regions of teleosts, including ATN and VTN, are connected to the Vs (Folgueira et al, 2004), which has been proposed as homologous to the medial amygdala (Biechl et al, 2017) (Kysil et al, 2017), and subordinate-dominant interactions (Pavlidis et al, 2011). CAS also elicits increases in cortisol responses in Nile tilapia (Silva et al, 2015) and zebrafish (Abreu et al, 2017a;Schirmer et al, 2013); interestingly, cortisol responses are also observed after visual contact with a predator in zebrafish (Barcellos et al, 2010(Barcellos et al, , 2007, and D. rerio also appears to be able to communicate predation risk to conspecifics, since cortisol responses are observed after seeing a shoalmate displaying antipredator behavior (Oliveira et al, , 2013. zebrafish lineage (gr s357 ) with non-functional glucocorticoid receptors.…”
Section: Hypothalamic Circuits For Defensementioning
confidence: 99%
“…Stimulation of the ATN elicits reproduction-related vocalizations in male midshipman fishPorichthys notatus(Goodson and Bass, 2000), suggesting a role in reproductive behavior; however, a role in defensive behavior has not yet been determined.Indirect evidence for a participation of the hypothalamus in defensive behavior is stronger in relation to neuroendocrine endpoints, especially cortisol responses, given that these responses are under descending hypothalamic control. Aversive stimuli which have been shown to elicit cortisol responses in zebrafish include acute chasing stress (deAbreu et al, 2016;Idalencio et al, 2017;Tran et al, 2014), acute restraint stress(Abreu et al, 2017a;Ghisleni et al, 2012), unpredictable chronic stress(Piato et al, 2011), exposure to the novel tank or the light/dark test…”
mentioning
confidence: 99%
“…The activation of the POA that is observed after CAS exposure is possibly related to the neuroendocrine profile that is observed in CAS‐exposed animals. Increases in cortisol levels were observed after CAS (Abreu et al ., ; Mathuru et al ., ; Schirmer et al ., ; Silva et al ., ) and disturbance signals (Barcellos et al ., , ; Oliveira et al ., , ; §9) in different species. Moreover, in D. rerio CAS elevates plasma levels of norepinephrine, epinephrine and glucose (Maximino et al ., ), strongly implicating the sympathetic system in these vegetative adjustments.…”
Section: Neural Bases Of the Alarm Reactionmentioning
confidence: 99%
“…Given that CAS is a partial predator stimulus that signals a potentially life‐threatening situation and induces sympathetic (Maximino et al ., ) and corticosteroid activity (Abreu et al ., ), it is possible that long‐term changes in behaviour after CAS exposure could be used to model post‐traumatic stress disorder (PTSD). PTSD presents two central features: exposure to an event that involves life‐threatening or serious injury to themselves or others, linked to intense fear, despair, or horror (Olff et al ., ; Miller & McEwen, ; Rao et al ., ).…”
Section: Applications Of the Alarm Reaction: Models For Panic Disordementioning
confidence: 99%
“…Differently from the behavior that is observed during exposure, behavior observed after exposure usually involves increased bottom dwelling associated with erratic swimming and freezing (Cachat et al, 2011;Egan et al, 2009) , analgesia (Maximino, 2011) , and increased dark preference associated with erratic swimming, freezing, and thigmotaxis (Maximino, Lima, Costa, Guedes, & Herculano, 2014) . Moreover, the alarm substance also produces intense autonomic resposnes, with increased plasma levels of glucose, haemoglobin, norepinephrine, and epinephrine (Maximino et al, 2014) , and a neuroendocrine stress response, with increased whole-body cortisol levels (Abreu, Giacomini, Koakoski, Piato, & Barcellos, 2017;Schirmer, Jesuthasan, & Mathuru, 2013). This array of behavioral and physiological adjustments simulate some important behavioral aspects and neurovegetative symptoms of panic attacks, lending…”
Section: Complementary Models: the Alarm Response Of Zebrafishmentioning
confidence: 99%